A boom-bust cycle in Ottoman Greece and the ceramic legacy of two Boeotian villages - Vionis, Athanasios K. (Journal of Greek Archaeology, 2016)
Asserting that scholarly obscurantism has hindered the evolution of Ottoman Archaeology during the new millennium in different parts of the Eastern Mediterranean would be a hyperbole. It is accurate to acknowledge though that research into the Ottoman past sprang out of Historical Archaeology through untangling its archaeological marginality only as late as the 1980s, when archaeologists and anthropologists started to appreciate the rich textual and material legacy of the Ottoman era in the framework of regional survey projects. Up until that time, the negative perception and unpopular legacy of the Muslim Ottoman Empire, the creation of national identities in the 19th and early 20th centuries, and the focus on the Biblical past, Iron Age kingdoms and Hellenic culture in present-day nation-states of the Eastern Mediterranean, such as Greece, Cyprus, Israel or even Turkey itself, did not encourage the growth and huge potential of Ottoman Archaeology as a discipline.